High-performance construction materials : science and applications - Shi, Caijun; Mo, Y. L. (Engineering materials for technological needs ;, 2008)
This book describes a number of high-performance construction materials, including concrete, steel, fiber-reinforced cement, fiber-reinforced plastics, polymeric materials, geosynthetics, masonry materials and coatings. It discusses the scientific bases for the manufacture and use of these high-performance materials. Testing and application examples are also included, in particular the application of relatively new high-performance construction materials to design practice. Most books dealing with construction materials typically address traditional materials only rather than high-performance m.